Development And Evaluation Of Hollow Microspheres Of Clarithromycin As A Gastroretentive Drug Delivery System Using Eudragit Polymers - APHALE SANJIVANI; SHINDE SWAPNILA; DHAT SHALAKA; BAGUL UDDHAV; SALUJA JAGDISH (International Journal of Pharma and Bio Sciences, 2011)
The present study deals with an attempt to develop hollow floating microspheres of Clarithromycin for gastro retention using Eudragit polymers prepared by emulsion solvent diffusion method. Eudragit S 100, RS 100, RL 100, L 100 and L 100 55 were used to prepare hollow microspheres. A drug – excipients compatibility study was performed using FTIR. The microspheres were characterized for shape and surface morphology by scanning electron microscopy. They were evaluated for particle size, flow properties, bulk density, % drug entrapment efficiency, floating properties and in-vitro drug release. The residual solvent content was determined after varying the stirring time. Drug to polymer ratio was varied from 1: 1 to 1: 3 and its effect on particle size and drug release was studied. The microspheres exhibited round shape, porous surface, prolonged drug release and buoyancy for more than eight hours. As the drug to polymer ratio increased the particle size increased and the drug release rate decreased.